Pengaruh Sertifikasi Halal Bagi Perkembangan Pelaku Usaha di Kota Bengkulu - Amiroh Rona Zakiyah; Khairiah Elwardah; Khozin Zaki (Economic Reviews Journal, 2025)
The aim of this research is to find out how halal certification affects business actors in Bengkulu City, consumer perceptions of halal-certified products, and the challenges faced by business actors in obtaining and maintaining halal certification. The method applied in this study is a qualitative approach, with data collection carried out through observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model. The findings of the study indicate that the impact of halal certification varies; 2 out of 5 business actors feel that they have not experienced an increase in their business due to dependence on seasonal markets. Halal certification has a positive impact on consumer trust, where 4 out of 7 consumers consider it important, although 3 out of 7 other consumers pay less attention to it. The main challenges faced by business actors include understanding the certification process, costs, and the obligation to renew the certificate.